O USO DAS TECNOLOGIAS DA INFORMAÇÃO E COMUNICAÇÃO NO CAMPO OPERACIONAL DA GUARDA CIVIL METROPOLITANA DE SÃO PAULO DESAFIOS À GESTÃO DE PESSOAS - Almeida, Jeane dos Santos (2009)
This thesis presents an exploratory study on the experience of implementing a system of digital security. The study had the locus of the Civil Guard Metropolitan Sao Paulo and general objective of the research is to examine the use of information and communication technologies in the organization's operational. First a literature search was performed for screening of similar themes. It was possible to verify the lack of studies on information and communication technologies in the Public Security in Brazil. Of the rare works that has found the inspiration for this research was the experiment conducted in Brasilia, in the area of Knowledge Management and Information Technology, which investigated the integration of information systems in the Federal District Public Security. For this case study adopted the methodology with qualitative research literature, documentary and field (interviews and direct observation). The results demonstrate the need for investment in information and communication technologies, to the integration and interoperability of organizations of Public Security. The results also confirmed the findings in research and studies on urban violence that indicate that only investment in technical infrastructure, in staff, management of safety, called the policy of combating violence and crime, not solve. We need urgency in integrated management of public policies to combat the causes of violence and provocative crime that are increasing poverty, unemployment, lack of efficient public services, particularly in the health sector and education, and lack of social policies, all seen as violence.(AU)